The Levy : Funding the Legal Services Oversight Commissioner : Consultation on the proposed regulations to be made under Sections 5 and 6 of the Legal Complaints and Regulation (Northern Ireland) Act 2016.: Funding the Legal Services Oversight Commissioner : Consultation on the proposed regulations to be made under Sections 5 and 6 of the Legal Complaints and Regulation (Northern Ireland) Act 2016. ([2017]) - Northern Ireland., Department of Finance,
No abstract available